Assessing the promise of biofortification: A case study of high provitamin A maize in Zambia - Lividini, Keith; Fiedler, John L. (Elsevier, 2015)
Biofortification is the breeding of new varieties of staple foods for increased micronutrient content. It is seen primarily as a complementary, rural-targeted strategy for better reaching remote populations. This paper presents an ex ante analysis of HarvestPlus' provitamin A maize (PVAM) in Zambia and highlights an empirical approach based on the Zambian 2005/06 Living Conditions Monitoring Survey (LCMS). Because more than 115 countries regularly conduct a Household Consumption and Expenditure Survey (HCES), the approach developed in this LCMS-based study can be applied in many other countries to analyze varietal adoption and conduct ex ante studies. Data from the LCMS and health statistics were used to characterize baseline indicators of vitamin A intake and Disability Adjusted Life Years (DALYs) lost. The introduction and scaling up of PVAM was modeled based on program plans, expert opinion and data on key adoption parameters. An adoption function was specified and expressed in terms of the percent of farmers expected to adopt PVAM over the next 30 years. A logistic regression adoption function was estimated and used to identify the specific LCMS households adopting, producing and consuming PVAM each year. Information from the IFPRI International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT) of yearly maize production and demand were used to produce annual estimates of PVAM planted, harvested and consumed. Taking into account an LCMS-empirically-informed, specified market structure, individuals' additional vitamin A intake was calculated. The number of DALYs saved were estimated using the change in vitamin A intake. Combining these estimates with cost data, the cost-effectiveness of PVAM was calculated. Assuming an adoption ceiling of 20% over 30 years, implementation of PVAM will result in average additional intake of 12% of the Estimated Average Requirement (EAR), a 3 percentage point reduction in the prevalence of inadequate intake, and savings of 23% of total DALYs. Impacts are concentrated among farming households that have adopted PVAM and consume it from their own production. Their consumption will result in an average additional vitamin A intake of 172 μg/day, more than 3 times the additional 54 μg/day among the entire population. Among this group, the reduction in the prevalence of inadequate intake will be more than 5 times the national average (17.5 percentage points). Valuing a DALY at $1000, PVAM's cumulative value of DALYs saved comes to exceed its cumulative total costs starting in 2019. Over 30 years the cost-effectiveness of PVAM in Zambia was estimated to be $24 per DALY saved, making it very cost-effective. The methodologies employed in this study provide insights and inputs that can be used to target farmers who are most likely to adopt, to measure their vitamin A intake and to craft messages to promote adoption. PVAM is a long term investment that shows great promise in becoming a highly cost-effective addition to the public health arsenal for combatting micronutrient deficiencies if the 20% adoption rate can be achieved and maintained. Doing so will require effective marketing strategies, including efforts to couple this nutrition-sensitive intervention with nutrition-specific activities, such as targeted nutrition messaging and education, in order to increase the likelihood that adopting farmers will prioritize production for home consumption.